Analisis Praktik Mudharabah pada Pedagang di Kota Purwakarta - Hisny Fajrussalam; Ananda Ananda; Kholic Kholic; Nida Nur Affisah (Departement of Mathematics Education, 2023)
Mudharabah is a profit sharing from the cooperation between two parties, the first party (shahibul maal) provides one hundred percent of the necessities, while the second party becomes the one who manage the necessities and share the profits in accordance with the mutual agreement agreement. In mudharabah contract, the financier or investor is not allowed to interfere in managing the business, when the mudharabah contract has been enforced. The research method used is descriptive research. Researchers conducted interviews with several street vendors to get information from sources directly. In addition, research evidence was carried out with documentation containing photos during observation and interview activities.